2020
DOI: 10.3390/nu12030694
|View full text |Cite
|
Sign up to set email alerts
|

Association between Soft Drink Consumption and Aggressive Behaviour among a Quarter Million Adolescents from 64 Countries Based on the Global School-Based Student Health Survey (GSHS)

Abstract: Soft drink consumption has become a significant public health concern that is associated with various adverse health outcomes. We aim to examine the association between soft drink consumption and aggressive behavior among adolescents. We used open access data from 79 studies in 64 countries, including 263,890 adolescents aged 12–18 years who completed the global school-based student health survey (GSHS). Self-reported data on past 30-day carbonated soft drink consumption (number of times per day) and past 12-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In examining the association of consumption of carbonated soft drinks and fast foods with stress-related sleep disturbance for males and females separately, a set of covariates was initially considered including age, food insecurity, BMI, smoking, alcohol intake, loneliness, and number of close friends, as informed by the current literature [24] . Before conducting multivariable modelling, the collinearity of the potential covariates was examined.…”
Section: Methodsmentioning
confidence: 99%
“…In examining the association of consumption of carbonated soft drinks and fast foods with stress-related sleep disturbance for males and females separately, a set of covariates was initially considered including age, food insecurity, BMI, smoking, alcohol intake, loneliness, and number of close friends, as informed by the current literature [24] . Before conducting multivariable modelling, the collinearity of the potential covariates was examined.…”
Section: Methodsmentioning
confidence: 99%
“…In line with the literature, our findings showed that the higher the frequency of sweet/salty snacks and soft drinks consumption, the higher the likelihood of preadolescents being afflicted by loneliness and aggression. Particularly, cross-sectional [ 35 , 36 ] and longitudinal studies [ 37 ] suggest a positive association between soft drinks consumption among adolescents and the expression of both aggressive behaviors [ 38 ] and loneliness [ 39 , 40 ]. However, in another cross-sectional study consisting of a sample of 13,486 children and adolescents, results showed a significant association between aggression and intake of sweetened beverages and snacks but sweets [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis, daily frequency of fresh fruit and vegetable intake was recoded to a continuous variable and categorised as 0 = did not eat, 0·5 =< 1 time/d, 1 = 1 time/d, 2 = 2 times/d, 3 = 3 times/d, 4 = 4 times/d and 5·5 = 5 or more times/d, respectively, as used elsewhere (32) . Daily frequency of carbonated soft drink intake was assessed with a single question ‘During the past 30 d, how many times per day did you usually drink carbonated soft drinks?’ ‘less than 1 time/d’, ‘1–2 times/d’, ‘3–4 times/d’, ‘5–6 times/d’, ’7–9 times/d’ and ‘10 or more times/d’ (31) .…”
Section: Methodsmentioning
confidence: 99%
“…Coke, Fanta and 7Up), and the students were instructed not to include diet soft drinks. In the analysis, soft drink consumption was recoded to a continuous variable and categorised as 0 = none/d, 1•5 = 1-2 times/d, 3•5 = 3-4 times/d, 5•5 = 5-6 times/d, 8 = 7-9 times/d, and 11 = 10 or more times/d, respectively (32) .…”
Section: Outcomes Measuresmentioning
confidence: 99%